CLOU process performance with a Cu-Mn oxygen carrier in the combustion of different types of coal with CO2 capture. (15th January 2018) - Adánez-Rubio, Iñaki; Abad, Alberto; Gayán, Pilar; de Diego, Luis F.; Adánez, Juan
Graphical abstract: Highlights: Combustion of coals with different rank was carried out in a CLOU unit. Cu-Mn mixed oxide prepared by spray granulation was the oxygen carrier. Complete combustion to CO2 and H2 O in the fuel reactor was achieved with all coals. A maximun in the CO2 capture efficiency was found with the solids circualtion rate. A high oxygen carrier to fuel ratio is beneficial for the oxygen carrier lifetime. Abstract: The Chemical Looping with Oxygen Uncoupling (CLOU) process is a Chemical Looping Combustion (CLC) technology that allows the combustion of solid fuels with inherent CO2 separation by using oxygen carriers based on metal oxides. This technology has a low energy penalty and thus low CO2 capture costs. The oxygen carrier used in the CLOU process must be able to release gaseous oxygen, an aspect that limits the availability of metal oxides for this process. This work investigated the suitability of an oxygen carrier containing 34 wt% CuO and 66 wt% Mn3 O4 (active phase Cu1.5 Mn1.5 O4 ) prepared by granulation regarding the CO2 capture, combustion efficiency and lifetime of the particles. The effect of the different types of coal (two sub-bituminous and a lignite) on combustion and CO2 capture efficiencies by CLOU was studied at different oxygen carrier to coal ratios in a continuous 1.5 kWth rig. It was found that full combustion could be reached regardless of the coal used. However, CO2 capture efficiencies were highly determined by coal rank. Finally, it was found that working with oxygen carrier to coal ratios higher than ϕ = 4, which corresponded to values of the variation of the oxygen carrier conversion lower than Δ Xoc  = 0.25, decreased the effect of chemical stress on the attrition rate. Therefore, it is clearly beneficial for the lifetime of oxygen carrier particles to operate with low variations of the oxygen carrier conversion (Δ Xoc ) between fuel and air reactors.